Individual learner differences: The relative contribution of learning strategies in language learning - Berry, Rita S. Y. (Journal of Modern Languages, 2002)
It is generally agreed that there is considerable variation among individuals in the ability to acquire/learn second languages. Some individuals seem to acquire their second language (L2) without much difficulty and they manage to master the language in a comparative short period of time. Others, on the contrary, tend to make slow progress over language learning even though a great deal of conscious effort has been spent on it. This has interested many researchers and consequently triggered a number of studies looking into how learners differ in language learning and what contributes to the differences. The results of these studies show that there are a number of dimensions of learner differences generally acknowledged, namely, age, affective states, beliefs, culture, language aptitude, learner attitudes, learning style, learning strategies, motivation, and personality. Although knowledge of individual learner differences (IDs) has been advancing, a comprehensive theory of IDs in second language acquisition is still lacking (Skehan 1991). There is a need to identify those IDs that are important for successful learning, to indicate the relative contribution of particular IDs to learning, to account for their influence on the learner’s choice of specific strategies, and to account for the effect (if any) IDs have on the process ofL2 acquisition (Ellis 1994:523). This paper aims to look into the relative contribution of one particular ID variable learning strategies towards language learning. The investigation to be reported looked into the ways second language learners differed in tackling their learning problems, from the perspective of language learning strategies. A few cases will be used to illustrate this and some attention will be directed towards how the learners’ strategy use had affected their learning process and language outcomes.